Morphological studies on the agglomeration of FeCo supported nitrogen-doped reduced graphene oxide catalyst prepared at varying annealing temperature - Shuaiba Samad,; Yusra Nadzirah Yusoff,; Loh, Kee Shyuan; Wong, Wai Yin (Penerbit Universiti Kebangsaan Malaysia, 2018)
One of the barriers to the large-scale commercialization of proton exchange membrane fuel cells (PEMFCs) is the high-priced of noble metals such as platinum (Pt). Therefore, in this paper, bimetallic electrocatalyst FeCo supported nitrogen-doped reduced graphene oxide (FeCo-NG) for oxygen reduction reaction (ORR) is proposed and has been successfully prepared through annealing of a mixture containing Fe, Co salts, dicyandiamide (DCDA) and graphene oxide (GO). The starting material GO appeared to be in multilayer sheets through scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analysis. Due to the high annealing temperature and the absence of the surfactant, agglomeration of FeCo nanoparticles was observed from the morphology analysis. The macrostructure size of the metals particles was observed to be increased over temperature. As the temperature increases, the agglomeration gets more intense because of the increased of van der Waals cohesive forces between the nanoparticles. In addition, the weak electrostatic interaction between the metal cations with the nitrogen and the GO sheets could also be the cause of the agglomeration. The weak electrostatic interaction caused the nanoparticles (Fe and Co) not attracted onto the GO sheets thus inhibit the reduction of FeCo and GO to occur in situ simultaneously. It is believed that the agglomeration of the electrocatalyst FeCo-NG could results to poor electrocatalytic activity of PEMFC.